Study of water droplet impinging on surface - Chan, Lester Wei Jian (Nanyang Technological University, 2018)
This report is based on the study of a water droplet impinging on a surface of different wettability and angle of impact. The drop characteristics were captured using a Phantom V711 digital high speed camera which was able to classify and quantify the high speed movements of the water droplet; the camera is able to capture as much as a million frames per second and this allows researchers to breakdown the high speed motion of the droplet. In this study of the impingement of water droplets, the experiments were conducted for based on different surface wettabilities, the Weber number of the droplet, and the angle of impact. The results were collected, closely inspected and analysed. The effect of the Weber number on the droplet impingement characteristics are summarised and reported.